A philosophy of breeding strategy for tropical forest trees - Namkoong, G; Barnes, R; Burley, J (Commenwealth Forestry Institute, University of Oxford, 1980)
Economic yields per hectare in forestry are low compared with agriculture and trees must be adapted to a far wider range of conditions. However, the area of potential production for forestry is often large and even small improvements in establishment or productivity may be very significant at the national level both in terms of social benefits and in terms of land values and the production of raw material for industry. There has, therefore, been very wide interest and participation in selective breeding of commercial forest trees in the last few decades when gains as high as 30% in value have been made in the first generation of selection. Breeding strategy, however, has not generally evolved to ensure flexibility and continued advance in future generations. This advance is dependent not only upon imaginative development of methods and materials, but also upon training and the development of skills in the human resource. Selection starts at the species/provenance/population level. Most species, and particularly those in the tropics, show patterns of variation over their natural range Which are indicators of vast genetic variation which can be released by breeders. The problems lie in our ability to observe variation, in the difficulty of recognizing potential useful gene combinations that may only become useful as requirements change in the future, and in the dangers of loss of variation through forest destruction. Planned sampling in programmes of selection may be cursory or intensive depending on information available for the species, on its variability and on its present and predicted economic importance. Because of lack of knowledge, it is almost always impossible to design optimum procedures and these programmes must be planned to yield both materials and information and some redundant sampling must be a~cepted. A sample of SO individuals could be expected to provide high security against losing genes and would preserve genetic variances and means in a population. The key feature of breeding within a population is the recurrent and cumulative nature of genetic improvement. Provided effective population sizes (Ne) are kept over 50, many generations of gain can be achieved and yields increased beyond the extremes of the present population. The rate of gain is dependent upon the amount of information and materials that the breeding method provides. The more rapid growth and shorter breeding cycles found in tropical species, coupled with the use of juvenile-mature relationships, genotype-environment interaction, elegance in experimental design and perceptive data collection, can make progress very rapid indeed. The breeder's dilemma is that, through intensive selection, he can make rapid gains but if Ne is reduced much below 20, future gain and flexibility are shut off. The option of backcrossing to re-introduce variation is not practical for the tree breeder because of the long breeding cycle. Breeding strategy at the population level has been termed 'meta-breeding' and it concerns the process of long-term genetic improvement through management and development of an array of population varieties. Through sampling variation, differences in selection criteria or uncontrolled error, genetic gain will not be the same in these popu1ations and if there is loss of variation within them, or a change in future requirements, recombination among them would regenerate variation and increase gains. Administrative and political constraints can be severe hindrances to the development of breeding strategy. Programmes for genetic improvement are long term and there is a need for continuity of staff, facilities and financing. There is also a need for national and international cooperation; real mutual benefits can be realised in the acquisition of materials and information, in obtaining advice and in the development of personnel. In this book a philosophy of tree breeding is prescribed that will stimulate imaginative initiative by individual breeders to obtain economically acceptable gains while maintaining flexibility for future generations of man, trees, environments and markets.